Drying and Energy Technologies - Delgado, J.M.P.Q; Barbosa de Lima, A. Gilson (Advanced Structured Materials,, 2016)
This book provides a comprehensive overview of essential topics related to conventional and advanced drying and energy technologies, especially motivated by increased industry and academic interest. The main topics discussed are: theory and applications of drying, emerging topics in drying technology, innovations and trends in drying, thermo-hydro-chemical-mechanical behaviors of porous materials in drying, and drying equipment and energy. Since the topics covered are inter- and multi-disciplinary, the book offers an excellent source of information for engineers, energy specialists, scientists, researchers, graduate students, and leaders of industrial companies. This book is divided into several chapters focusing on the engineering, science and technology applied in essential industrial processes used for raw materials and products.